TALABALARǴA ÁMELIY JUMISLARDI ORINLAWDA QOLLANILATUǴIN INTERAKTIV USILLAR HAQQINDA MAǴLIWMATLAR - Qazaxbaev, S. (SCIENCE and SOCIETY, 2023)
The article deals with the use of interactive methods at the foreign lessons. The author determines the foreign lessons. The author determines the teacher’s task in formation of habits to use certain strategy, tactics and methods at different stages of creative activity. The author gives the quotations of different scholars.